2022
DOI: 10.4012/dmj.2022-100
|View full text |Cite
|
Sign up to set email alerts
|

Two-body wear and surface hardness of occlusal splint materials

Abstract: The aim of this in vitro study was to evaluate the wear and surface hardness of nine materials for conventional manufacturing, subtractive milling, and 3D printing of occlusal splints, as well as to evaluate the differences in wear and surface hardness between rigid and flexible 3D-printed occlusal splint materials. Two-body wear and Vickers hardness tests were performed. The vertical wear depth and Vickers hardness values were statistically analyzed. Vertical wear depth and surface hardness values were statis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
(65 reference statements)
2
12
0
Order By: Relevance
“…To conclude, 3D-printed materials have lower surface hardness values in comparison with conventional materials [ 2 , 3 , 5 ] ( Figure 3 ). These results could be clarified by the layer deposition, which was parallel to the loading orientation in the 3D-printing techniques, leading to low mechanical properties, as well as the fact that the strength of adhesion between subsequent layers is less than the strength of each individual layer [ 2 ]. Differences between different materials and fabrication techniques should be taken into account when choosing the optimal solution for the treatment of patients.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…To conclude, 3D-printed materials have lower surface hardness values in comparison with conventional materials [ 2 , 3 , 5 ] ( Figure 3 ). These results could be clarified by the layer deposition, which was parallel to the loading orientation in the 3D-printing techniques, leading to low mechanical properties, as well as the fact that the strength of adhesion between subsequent layers is less than the strength of each individual layer [ 2 ]. Differences between different materials and fabrication techniques should be taken into account when choosing the optimal solution for the treatment of patients.…”
Section: Discussionmentioning
confidence: 92%
“…Based on the present study’s findings, milled materials for occlusal splint fabrication showed superior mechanical properties ( Figure 2 and Figure 3 ) and can be highlighted as optimal materials for the manufacturing process. Nevertheless, present and future developments in the field of additive manufacturing could bring novel 3D-printed materials with mechanical properties that could compete with those of other materials and processing techniques; however, for now, modern 3D-printed materials are generally inferior ( Figure 2 and Figure 3 ) [ 2 , 3 , 5 ]. However, 3D-printed materials could be used in short-term therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was concluded that the PMMA-based splint materials showed surface hardness and uniformity in wear resistance, regardless of the manufacturing technology, while the 3D-printed light-curing resin material showed lower surface hardness and higher wear. This may be due to the layers that are deposited parallel to the direction of the load and the adhesion between successive layers [ 23 ]. In our study, the printed materials presented lower values than the milled ones; however, the flexural rigid material could present less possibility of fracture than a conventional one and also, for the same reasons stated above, less possibility of wear in the face of function or parafunction, although this should be corroborated by additional studies.…”
Section: Discussionmentioning
confidence: 99%